2018
DOI: 10.1108/jwl-11-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of leadership inspiration, rewards and its relationship with contribution to knowledge sharing

Abstract: Purpose The purpose of this paper is to examine the impact of leadership and rewards on the contribution to knowledge sharing in public organizations of the United Arab Emirates (UAE). Design/methodology/approach Data were collected from 154 employees from various organizational units of a law enforcement organization in the UAE, and structural equation modeling was used to test the proposed hypotheses. Findings Leadership inspiration was found to be positively effective in enhancing the contribution of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…, 2011). This increases the chances for the creation and maintenance of a safe psychosocial climate, which, in turn, is a moderator for increasing a creative team climate for innovativeness at work (Al Dari et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2011). This increases the chances for the creation and maintenance of a safe psychosocial climate, which, in turn, is a moderator for increasing a creative team climate for innovativeness at work (Al Dari et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is proactive, clarifies objectives and provides support, empowerment, and encouragement to the team (Latif et al, 2017;Rosing et al, 2011). This increases the chances for the creation and maintenance of a safe psychosocial climate, which, in turn, is a moderator for increasing a creative team climate for innovativeness at work (Al Dari et al, 2018). The poor development of the ambidextrous leadership-related literature over the last decade indicates that it is still little understood.…”
Section: Discussionmentioning
confidence: 99%
“…Mehrajunnisa and Jabeen (2020) investigated strategic drivers that can enhance employee suggestion schemes in the UAE. Moreover, knowledge sharing in public organizations of the UAE was investigated by Al Dari et al (2018). Moreover, Jabeen and Al Dari (2020) developed a framework for integrating knowledge management benefits in the UAE organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Harvey (2012) reported that the aging workforce, particularly in developed countries, raises concerns that the knowledge of these older and more experienced employees may vanish when they retire. Al Dari et al (2018) affirmed that the inspirational leader will succeed in leading the employees and increasing knowledge sharing. The process of knowledge exchange is a precursor of organizational learning (Islam et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%